Mid-transverse colon cancer and extended versus transverse colectomy: Results of the Italian society of surgical oncology colorectal cancer network (SICO CCN) multicenter collaborative study. Issue 9 (September 2020) - Milone, M.; Degiuli, M.; Allaix, M.E.; Ammirati, C.A.; Anania, G.; Barberis, A.; Belli, A.; Bianchi, P.P.; Bianco, F.; Bombardini, C.; Burati, M.; Cavaliere, D.; et al.
Abstract: Introduction: Transverse colon cancer (TCC) is poorly studied, and TCC cases are often excluded from large prospective randomized trials because of their complexity and their potentially high complication rate. The best surgical approach for TCC has yet to be established. The aim of this large retrospective multicenter Italian series is to investigate the advantages and disadvantages of both hemicolectomy and transverse colectomy in order to identify the best surgical approach. Materials and methods: This was a retrospective cohort study of patients with mid-transverse colon cancer treated with a segmental colon resection or an extended hemicolectomy (right or left) between 2006 and 2016 in 28 high-volume (more than 70 procedures/year) Italian referral centers for colorectal surgery. Results: The study included 1529 patients, 388 of whom underwent a segmental resection while 1141 underwent an extended resection. A higher number of complications has been reported in the segmental group than in the extended group (30.1% versus 23.6%; p 0.010). In 42 cases the main complication was the anastomotic leak (4.4% versus 2.2%; p 0.020). Recovery outcomes also showed statistical differences: time to first flatus (p 0.014), time to first mobilization (p 0.040), and overall hospital stay (p < 0.001) were significantly shorter in the extended group. Even if overall survival were similar between the groups (95.1% versus 97%; p 0.384), 3-year disease-free survival worsened after segmental resection (78.1% versus 86.2%; p 0.001). Conclusions: According to our results, an extended right colon resection for TCC seems to be surgically safer and more oncologically valid.